2018
DOI: 10.18632/oncotarget.24190
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone-induced activation of mTORC1 and inhibition of autophagy contribute to skeletal muscle insulin resistance in a mouse model of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age and also an important metabolic disorder associated with insulin resistance (IR). Hyperandrogenism is a key feature of PCOS. However, whether hyperandrogenism can cause IR in PCOS remains largely unknown. The mammalian target of rapamycin complex 1 (mTORC1) and its regulated autophagy are closely associated with IR. In the present study, we investigated the role of mTORC1-autophagy pathway in skeletal muscle IR in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…(2018) who stated that DHEA induced PCOS due to its effects on the hormones responsible for androgen balance, glucose homeostasis, and regulation of follicular growth. Coinciding with our results, it was found that DHEA increases androgen production which in turn may promote insulin resistance through elevated FBG, HbA1c, and fasting plasma insulin levels associated with increased HOMA‐IR index compared to the control group (Song et al., 2018). Also, DHEA was reported to increase LH production in the pituitary gland and the hypothalamus which may increase the estrogen level which is one of the prominent characteristics of PCOS (Xia et al., 2017).…”
Section: Discussionsupporting
confidence: 89%
“…(2018) who stated that DHEA induced PCOS due to its effects on the hormones responsible for androgen balance, glucose homeostasis, and regulation of follicular growth. Coinciding with our results, it was found that DHEA increases androgen production which in turn may promote insulin resistance through elevated FBG, HbA1c, and fasting plasma insulin levels associated with increased HOMA‐IR index compared to the control group (Song et al., 2018). Also, DHEA was reported to increase LH production in the pituitary gland and the hypothalamus which may increase the estrogen level which is one of the prominent characteristics of PCOS (Xia et al., 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, it has been shown that the promotion of autophagy could improve insulin resistance in nonalcoholic steatohepatitis (Amir and Czaja 2011), suggesting that modulation of autophagy tightly connected to insulin resistance. Additionally, overexpression of key autophagy regulatory protein mechanistic target of rapamycin kinase (mTOR) can lead to insulin resistance during the pathological development of PCOS (Liu et al 2018;Song et al 2018). Besides, mitochondrial dysfunction and ER stress have been shown to participate in the pathogenesis of PCOS (Azhary et al 2020;Zeng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A higher proportion of type I fibers leads to better insulin responsiveness. Taken together, the data from the present study further supported mitochondrial dysfunction in the skeletal muscle of DHEA‐induced PCOS mice that we have recently shown (Song et al, ). It is still controversial as to the role of mitochondrial dysfunction in skeletal muscle IR in women with PCOS.…”
Section: Discussionmentioning
confidence: 95%
“…Skeletal muscles are thus capable of locally synthesizing sex steroid hormones. We have recently shown that the testosterone level in the skeletal muscle was significantly higher in DHEA mice than in controls, whereas the estradiol level was similar between the two groups of animals (Song et al, ). The upregulated testosterone level in the skeletal muscle is possibly due to the increased circulating DHEA.…”
Section: Discussionmentioning
confidence: 99%